2015
DOI: 10.5455/ijmsph.2015.03032015166
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of medical students toward serving in rural areas and its determinants: a cross-sectional study from Uttarakhand

Abstract: public health indicators and/or weak infrastructure. Uttarakhand is one of these. The first contact of village community with a medical officer occurs at a primary health center (PHC). The PHCs were envisaged to provide an integrated curative and preventive health care to the rural population with emphasis on preventive and promotive aspects of health care. The PHCs are established and maintained by the state governments under the Minimum Needs Programme/Basic Minimum Services (BMS) program. As per minimum req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
(3 reference statements)
3
3
0
Order By: Relevance
“…In the present study, only 14% of interns showed positive attitude towards compulsory rural health services whereas in a study done by Gaikwad et al it was 44%. 4 In the present study, the most common reasons for positive attitude being that it provides a good exposure for general practice and an opportunity for independent working which were similar to the findings observed by Singh et al 2 The most common reasons for negative attitude observed in the current study were, isolation from family and relatives, inadequate hospital infrastructure and poor connectivity with cities whereas in a study done by Dutt et al the reasons were lack of clinical guidance, poor basic needs, no career growth and heavy work load. 1 Present study observed that interns staying in rural locality had a more positive attitude towards rural services than those staying in urban locality and this association was found to be statistically significant…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, only 14% of interns showed positive attitude towards compulsory rural health services whereas in a study done by Gaikwad et al it was 44%. 4 In the present study, the most common reasons for positive attitude being that it provides a good exposure for general practice and an opportunity for independent working which were similar to the findings observed by Singh et al 2 The most common reasons for negative attitude observed in the current study were, isolation from family and relatives, inadequate hospital infrastructure and poor connectivity with cities whereas in a study done by Dutt et al the reasons were lack of clinical guidance, poor basic needs, no career growth and heavy work load. 1 Present study observed that interns staying in rural locality had a more positive attitude towards rural services than those staying in urban locality and this association was found to be statistically significant…”
Section: Discussionsupporting
confidence: 89%
“…(p=0.03) which is similar to the findings observed by Singh et al2 No association was found between gender and attitude towards rural health services in the present study and similar findings were observed by Deressa et al6 …”
supporting
confidence: 92%
See 1 more Smart Citation
“…Rural background and primary education at rural areas were identified as the strong variable associated with the retention of health professionals in rural communities by various literatures. 7,10,13,14 This can be explained by the familiarity of medical students with rural setting and cultural norms. We observed that medical students with well-educated parents had less favourable attitude towards working at rural areas similar to study conducted by Saini et al 7 and Singh et al 14 Medical students from I st and II nd years of undergraduation showed more willingness to work in rural area may be because of poor knowledge regarding working conditions in rural area.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,13,14 This can be explained by the familiarity of medical students with rural setting and cultural norms. We observed that medical students with well-educated parents had less favourable attitude towards working at rural areas similar to study conducted by Saini et al 7 and Singh et al 14 Medical students from I st and II nd years of undergraduation showed more willingness to work in rural area may be because of poor knowledge regarding working conditions in rural area. 14 For the medical students who were interested to work in rural area, the major reason for that decision was to provide service to the poor/underprivileged (social service) as there is scarcity of health care facilities in rural area.…”
Section: Discussionmentioning
confidence: 99%